The Earth and its People: Repairing Broken Connections - Nowlan, Godfrey (Geoscience Canada, 2001)
Summary Humans are losing touch with the Earth. They tend to ignore the strong linkages between earth resources and the level of civilization they enjoy. They also tend to ignore the forces of earth processes, rendering themselves insensitive to natural processes and hazards. The disconnection is strongest in the developed, first world of which Canada is a part. Earth scientists hold the key knowledge to repair this disconnection between the Earth and its people. It is critical that we place more of a social context on earth science, especially as it is communicated to the public. We need to re-establish the connections between our well-being and the earth resources that make it possible. We also need to educate society about how Earth processes affect our everyday life. By the same token, we also need to elaborate more of the social context of earth sciences to students of earth sciences.